The role of executive function in cognitive reappraisal: a meta-analytic review - Toh, Wei Xing (2024)
Cognitive reappraisal refers to the reinterpretation of a situation to alter its emotional meaning. Theoretically, executive functions (EFs), such as inhibition, updating, and shifting, are core elements of reappraisal processes. However, empirical studies have yielded inconsistent evidence as to whether and to what extent EFs are associated with reappraisal. To address this issue, we conducted a meta-analysis of the literature in which 179 effect sizes from 59 independent samples (N = 4,703) were included. Using random-effects metaregression with robust-variance estimates and small-sample corrections, we also examined whether variation in effect sizes could be accounted for by potential moderators, such as the way reappraisal was assessed (i.e., questionnaires vs. task-based measures) and the type of stimuli used in EF tasks (i.e., affective vs. nonaffective). Overall, results indicate relatively small to typical associations between reappraisal and all three EFs (rs = .13–.19). While the way reappraisal was measured did not moderate any of the relations between EF and reappraisal, we found stronger relations between inhibition and reappraisal when EF was assessed using tasks that involved affective, relative to nonaffective, stimuli. Our meta-analytic findings offer modest support for the idea that EFs are cognitive constituents of reappraisal processes.